Pengaruh Minat Baca dan Ketersediaan Sumber Belajar Terhadap Prestasi Belajar Siswa Kelas IV SDN Centre Mangalli - Rosdiah Salam; Kiki Kiki; Hikmawati Usman (STKIP Andi Matappa Pangkep, 2023)
This research uses a quantitative approach with an ex-post facto type of research and uses a partial test research design (t-test) which aims to determine the influence of reading interest and the availability of learning resources on the Learning Achievement of Class IV Students. The population in this study was 30 grade IV students at SDN Center Mangalli. Data collection techniques in this research were taken using questionnaires, observation sheets and documentation. The data analysis techniques used are descriptive statistics, normality and partial tests (t-test). The results of the research carried out by the researcher show that the reading interest of class IV students is very high and the availability of learning resources is also very high or adequate and learning achievement, especially in Indonesian language subjects, is also in the very good category. The results of this research show that students' reading interest is included in the high and very high categories, availability of learning resources is included in the criteria of adequate or very good, student learning achievement is included in the achievement and very achievement categories, there is an influence of interest in reading and availability of learning resources on the learning achievement of class IV students.